A Comprehensive Review of Hypotheses About the Biological Function of Zearalenone, and a New Hypothesis for the Function of Resorcylic and Dihydroxyphenylacetic Macrolactones in Fungi - María Viñas; Petr Karlovsky (Toxins)
The special metabolite of Fusarium spp. zearalenone (ZEN) exerts estrogenic effects on mammals, stimulates plant growth, stimulates sexual development in fungi, and inhibits fungal growth. These activities inspired hypotheses about the biological function of ZEN. We briefly review the discovery of ZEN and its implications. The main subject of this review is a critical assessment of the hypotheses that ZEN is a fungal hormone, a plant hormone, a virulence factor, or a fungal defense metabolite. Conceptual and technical issues related to testing these hypotheses, such as inadequate analytical methods, confusion of incidental effects with biological functions, and lack of normalization, are illuminated. Based on these considerations, gene knockout experiments, and on the effects of biotic interactions on ZEN synthesis, we argue that ZEN is a defense metabolite protecting Fusarium spp. against mycoparasites and competitors. Similar reasoning and published data suggest that the Fusarium metabolite fusaristatin A fulfils the same function. Fungi produce many macrolactones of resorcylic acid (RALs) and dihydroxyphenylacetic acid (DHPLs) with properties similar to ZEN. Their widespread occurrence, antifungal activity, and further considerations prompt us to hypothesize that the fundamental function of fungal RALs and DHPLs lies in defense and interference competition.